If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3B + -4 = 26 Reorder the terms: -4 + 3B = 26 Solving -4 + 3B = 26 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 3B = 26 + 4 Combine like terms: -4 + 4 = 0 0 + 3B = 26 + 4 3B = 26 + 4 Combine like terms: 26 + 4 = 30 3B = 30 Divide each side by '3'. B = 10 Simplifying B = 10
| 3B+5=60 | | k^2-22k+105=0 | | 2/5s=11/5 | | 150=7n-2n | | 2/5y=6 | | 3B+-5=26 | | 5yz(-z)= | | -5/4m=-10 | | n/4=81 | | 5=-1+b | | 4y=-8(-2) | | 3(-b-11)+6=6b | | 2/9z=8 | | 35+n=217 | | 4y=-8(0) | | 35y=-105 | | x+3=1+x+2 | | n-29=-10 | | 8x+5=36x(2) | | 5/5=1 | | 88+n=303 | | 4y=-8(2) | | 2x+6=1+2x | | 218=4n-3n | | 23x=8(x+6) | | -41=n/13 | | 7(6x+10)=70 | | 11(10+j)=21j | | 10x+4x-8x-3x= | | 2(4x+1)=2 | | 272=3n+n | | 2(7x+7)=70 |